BAS/BSCR40 Coronary heart disease risk associated with the homozygous minor allele for endothelial protein C receptor Ser219Gly. Issue 17 (26th August 2010) - Ireland, H A; Cooper, J A; Talmud, P J; Hingorani, A D; Kivimki, M; Kumari, M; Morris, R; Tzoulaki, I; Price, J; Fowkes, F G; Humphries, S E
Abstract : Rationale for the study: Endothelial protein C receptor (EPCR) is involved in the regulation of thrombin generation and inflammation. PROCR gene variant rs867186 codes for an amino acid substitution (Ser219Gly) within the membrane spanning region of EPCR. The minor allele of the variant has been identified as functional, and associated with increased shedding of EPCR from the endothelial surface.1 Previous analysis has also shown increased coagulation activated markers in those with the Gly allele1.2 Furthermore, while heterozygotes for this variant may be protected from coronary heart disease (CHD), homozygotes had a threefold elevation in CHD risk in a prospective cohort (NPHSII).1 In a case–control study of CHD (HIFMECH), there was a suggestion that the EPCR genotype interacts with factors present in metabolic syndrome, to increase CHD risk.1 Methodology: NPHSII was analysed to further assess the CHD risk associated with EPCR Ser219Gly in those who have been identified as diabetic, or as having 'metabolic syndrome', during 15 years' follow-up. Results: Individuals who were Gly/Gly and had 'metabolic syndrome' had a fourfold increase in CHD risk compared with Ser/Ser (HR=4.72, CI 1.69 to 13.4) p=0.006; or an eightfold increase in risk above those who were Ser/Ser without metabolic syndrome (HR=8.02, CI 2.89 to 22.2) p=0.006. No Gly/Gly individuals without metabolic syndrome had a CHD event. Conclusions: Homozygotes for the Gly allele are present at a frequency of ∼1%. If the findings in the study can be replicated, the variant would constitute a considerable CHD risk in 1% of diabetics. Replication studies are under way in three further, large prospective cohorts.